Towards the development of smart weather routing systems for leisure planing boats. Issue 1 (1st December 2022) - Ciampolini, M; Balduzzi, F; Romani, L; Bellucci, L; Bianchini, A; Ferrara, G
Abstract: Weather routing (WR) systems are widely adopted in the maritime transport since safety of goods and saving of fuel are crucial for shipping companies. However, the need of protecting the local coasts and reducing CO2 emission is making WR attractive even for the market of leisure boats, especially if comfort and safety are also accounted. In the present study, a prototype of a WR system is presented. The developed tool implements the Dijkstra's algorithm to find the fuel-optimal path while ensuring comfort and safety. A computationally efficient digital twin of a planing boat, based on a 2D+t model and a powertrain mapped model, has been implemented for the estimation of the fuel consumption and the evaluation of vertical accelerations. The methodology for the acquisition of online weather data is presented, together with the strategy for the assessment of comfort and habitability. The application of the WR tool in a typical path of the Tuscan Archipelago shows improvements in fuel usage and comfort even in moderate weather conditions. The influence of each weather variable on fuel efficiency is assessed, highlighting the requirement of an accurate dynamic modelling. Criteria for the graph design are also outlined, showing a wrong estimation of comfort and fuel usage in case of low-definition graphs. The paper proves the potential and the effectiveness of the developed tool, moving toward a greener and more comfortable navigation in local seas.